Effect of Rhythmic Breathing on Pain Intensity during Insertion of Vascular Needles in Hemodialysis Patients - Seyed Reza Borzou; Sophia Akbari; Gholam-Hosein Falahinia; Hosein Mahjub (Tehran University of Medical Sciences, 2014)
Background & Aim: Patients with end-stage renal disease undergoing hemodialysis are repeatedly exposed to stress and pain from approximately 300 punctures per year to their arteriovenous fistula . Patient comfort with the procedure is therefore of greatest importance for long-term compliance with the treatment and until a successful renal transplant. This study was conducted to determine the effect of rhythmic breathing on pain intensity when the needles are inserted into vascular access for hemodialysis .   Methods & Materials: This was a quasi -experimental one-group time-series study. Thirty five patients in hemodialysis ward of Hamadan Besat hospital entered into the study via convenient sampling method. In this study, pain intensity during the insertion of hemodialysis vascular needles was measured in six sessions through two methods of routine intervention and rhythmic breathing. The data were collected using visual analog scale. Paired t-test was used to determine pain intensity mean difference between the two conditions .    Results: Overall, the results showed that the mean pain intensities were 5.45±1.15 and 2.19±0.92 in two conditions including routine intervention and rhythmic breathing , respectively. Paired t-test showed a significant difference between the routine intervention and rhythmic breathing (P<0.001) .   Conclusion: These findings showed that rhythmic breathing was effective in reducing pain when the needles were inserted into the vascular access. Therefore, it is recommended to use rhythmic breathing as a simple and non-expensive method to reduce pain in patients before insertion of hemodialysis vascular needles .